LIVING IN HARMONY BETWEEN MUSLIM AND BUDDHIST: Comparative Study: Indonesia and Southeast Asia - Watini Watini (Aceh Anthropological Journal, 2018)
This article attempts to describe connection between Indonesia and Southeast Asia also India. First part, it describes Islam Nusantara as one of Islam Indonesian style. Islam Indonesia is very close with tradition, for example Islam Aboge, Islam Ammatoa and Islam Java/Islam Kejawen. Islam Indonesia have relationship with tradition that some scholars perceived it as indigenous religion. So, after that part it is followed by Buddhism Nusantara style because particularly Islam Java have strong encounter with Buddhist tradition. The study is descriptive and qualitative research. This research looks at how Muslim and Buddhist relation is preserved in Southeast Asia. This research was standing in Muslim-Buddhist relation framework. Simplicity speaking, this paper shows that Indonesia have connection peacefully with other countries such as India and Southeast Asia. Since Islam came to Indonesia in 12-15th century, Islam encounter with Hindu Buddhist tradition but Islam can develop and make one style of Islam Indonesia/Islam Nusantara such as Islam Ammatoa, Islam Aboge and Islam Java.